Ultra-Technological Refugees: Identity Construction through Consumer Culture among African Refugees in Israel (Glocalism: Journal of Culture, Politics and Innovation, 2017)
Academic discourse tends to view the labor market as a central sphere in the refugee integration process, while other aspects related to the market economy, such as capital accumulation and the purchase of goods, gain less attention if at all. Studying these issues from the perspective of African refugees in Israel enables us to examine alternative means through which the refugee community seeks to integrate into the socio-economic arena in the host culture by adopting popular consumption patterns. The study explores consumer culture among refugees as a means through which they borrow, adopt and translate what they perceive to be the attributes of the desired lifestyle in the host country. Based on ethnographic work, the study examines the ways in which consumption practices form a socio-cultural bridge to blur social boundaries between refugees and Western society. By adopting commodity and consumption patterns, African refugees seek to become a part of the Israeli collective and distance themselves from the monolithic identity of alien-African-refugees.
Keywords: African Refugees; Consumer Culture; Identity; Globalization; Israel